The Role of Physical/Sporting Activities in Coping with Behaviour Problems among Primary School Students - Zurc, Joca; Jelovčan, Giuliana; Štemberger, Vesna (Revija za elementarno izobraževanje, 2022)
Physical/sporting activities provide a child with opportunities to interact with others, validate and express him/herself, while also being critical factors in socialisation and the prevention of deviant behaviour. Therefore, in this study, we were interested in which physical/sporting activities are most strongly associated with the management of behaviour problems. Results from a representative sample of 1782 Slovenian primary school students show that a lack of physical/sporting activity is the strongest predictor of internalising behaviour problems. In this context, key roles are played by the frequency and intensity of activity, extracurricular sports activities, practising dance and limiting sedentary transportation to school.
Keywords: primary school, discipline, hyperactivity, sport, healthy lifestyle.